تحليل المؤشرات التعليمية الزواجية في المحافظات السورية باستخدام طريقة تحليل المركبات الأساسية - الرفاعي عبد الهادي; حمادة عبد الله; بركات شروق (Latakia University Journal - Economic and Legal Sciences Series, 2019)
بهدف التعرف على مدى إمكانية تطبيق طريقة تحليل المركبات الأساسية على المؤشرات التعليمية الزواجية، وإلى أي حد يمكن تمثيل العديد من هذه المؤشرات بعدد أقل، سيتم أولاً التطرق إلى عملية تحليل البيانات الإحصائية ومدى أهميتها في مختلف البحوث العلمية، ومن ثم سيتم عرض لطريقة تحليل المركبات الأساسية ولأهم المفاهيم والمصطلحات المستخدمة فيها ومعايير استخراجها، وأهم الاستخدامات لقيمها، من ثم سيتم تطبيق تلك الطريقة على المؤشرات التعليمية الزواجية الموزعة على المحافظات السورية، بهدف تحديد المركبات الأساسية التي تمثل تلك المؤشرات أفضل تمثيل، وتفسر النسبة الأكبر من تباينها الكلي، ونتيجة ذلك تم التوصل إلى مركبين أساسين يمثلان المؤشرات التعليمية الزواجية المدروسة ويفسران ما نسبته 91% من تباينها الكلي، وسيتم الاستفادة من النتائج السابقة في تقديم بعض التوصيات التي نراها مهمة. To know the extent of possibility of applying of analyzing the Principal Components method on the Education marital indexes, and to what extent it could represent many of these marital indexes in a less number, firstly it will be referred to the process of analyzing the statistic data and its importance in different scientific researches, and then it will show the method of analyzing the Principal Components, the most important concepts and the used terms, the standards of getting them out in addition to the most important uses of its values, and then it will apply that way on the scattered education marital indexes in the Syrian cities to determine the Principal Components which represent these indexes in its best representation and explain the biggest ratio of the total variance. And as a result to this, there are two Principal Components which represent the studied indexes and explain 91% of the total variance, and it will make use of the previous results in offering some important recommendations as we see them.